Implementation Of Ecotheology In Smp Negeri 9 Kaur - Nina Anggita Ardani; Khusnul Khotima; Ranisa julia; Rosi Delta Fitrianah (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This research is motivated by the importance of applying ecotheological values in the world of education as an effort to foster students' awareness of environmental preservation in harmony with religious values. However, the implementation of ecotheology in the school environment still faces various challenges, such as low student awareness in maintaining cleanliness, lack of discipline in waste management, and limited understanding of the relationship between religious values and environmental conservation. In addition, the inadequate infrastructure and lack of consistent habituation are also obstacles in its implementation. This study aims to find out how the implementation of ecotheology in SMP Negeri 9 Kaur, the forms of activities carried out in its application, as well as the supporting and inhibiting factors in the implementation of ecotheology in the school. This study uses a qualitative approach with a descriptive method, through data collection techniques in the form of observation, interviews, and documentation. The results of the study show that the implementation of ecotheology at SMP Negeri 9 Kaur is carried out through various activities such as the habit of maintaining environmental cleanliness, waste management, reforestation activities, and the integration of religious values in learning. Supporting factors in the implementation of this program include the support of school principals, teachers, and the existence of an environment-based school policy. Meanwhile, the inhibiting factors are the low awareness of some students, limited facilities, and not optimal habituation on a sustainable basis.